Peningkatan Literasi Kesehatan Ibu Melalui Edukasi Imunisasi Dasar Anak di Wilayah Puskesmas Bontomarannu, Kabupaten Gowa - Indirah Maudy Miftahul Jannah; Arlina Wiyata Gama; Najamuddin Najamuddin; Rista Suryaningsih; Arifuddin Ahmad (Jurnal Pengabdian Ilmu Kesehatan, 2025)
: Incomplete immunization can cause morbidity and death due to diseases that should be prevented by immunization (PD3I). This study explores the correlation between maternal health literacy and compliance with basic immunization for children aged 0-11 months in Bontomarannu Community Health Center, Gowa Regency. This study design used a retrospective cross-sectional study for quantitative analysis with a total sample of 87 mothers. Research data was obtained from the results of filling out the HLS–EU–Q16 questionnaire and secondary data related to the completeness of child immunization. Research data was analyzed using the Chi Square test with the help of the SPSS program. The results of the analysis show that there is a significant relationship between health literacy and maternal compliance in providing basic immunizations to children (p-value = 0.000). Mothers with adequate health literacy tend to have high compliance in providing children with basic immunizations. The results of the analysis showed that of the 87 mothers studied, the majority of mothers with inadequate health literacy tended to be incomplete in providing basic immunizations to their children, while of all mothers with adequate health literacy, all provided complete basic immunizations. In conclusion, addressing health literacy is crucial for effective immunization programs.